Regulating Alternative Finance : Results from a Global Regulator Survey - World Bank; Cambridge Centre for Alternative Finance (World Bank, Washington, DC, 2019)
The survey aims to comprehensively and comparatively analyze how regulators from both developing and developed economies are regulating and supervising online alternative finance activities. The current gap is between the demand for finance by small and medium size enterprises (SMEs) and existing matching supply is estimated to be approximately $5 trillion worldwide. Fortunately, access to formal financial services has expanded tremendously over the past few years, fueled by Fintech solutions. Not only have they increased financial inclusion, they have also increased competition, driving prices lower and improving the quality of services offered. This momentum -driving access to transaction accounts and electronic payments- is crucial for financial inclusion, but firms and individuals also need access to credit, insurance, long-term savings and pension products and investment capital. This report focuses on peer-to-peer lending, equity crowdfunding and initial coin offerings, which constitute a rapidly growing segment of fintech for meeting credit, savings and investment needs. Survey findings informing this report are based on responses from regulators in more than one hundred and ten jurisdictions across the world. The survey identified expanded access to finance for firms and individuals and strengthened competition as primary triggers for advancing the development of alternative finance.